Financial Technology Acceptance in Baby Boomers Generation - Dwi Rizqa; Ichsan Adil Prayogi ‎ (Indra Institute Research & Publication, 2023)
The financial industry currently provides convenience things for its consumers because there is technology here that can be called financial technology (fintech). Various benefits can be provided by fintech. However, besides the benefits that can be provided by fintech, there are also those caused by the negative side of fintech. The existence of some negative things can affect people’s acceptance of fintech. Various kinds of fintech companies target their products to the millennial generation. The presence of the baby boomer generation is often ignored by marketing. Various factors cause baby boomers to lose from the target. It might be because baby boomers cannot accept technology or even need fintech to support their daily activities. This research needs to be done so that industry players especially in financial technology can understand the consumers that baby boomers can be accepting the technology. Therefore, the researchers conduct this research using a meta-analysis so can explain the reality that occurs. This research was conducted using qualitative - descriptive. The focus of this research is the acceptance of fintech in baby boomers generation.